Efecto del tamaño del explante sobre la tasa de multiplicación de plantas in vitro de cultivares de plátano. - Velasco Párraga, Andrea Alexandra (2019)
The multiplication of musaceous plants through the in vitro culture of tissues, has allowed the massive reproduction of plants to supply the demand of required planting material, especially banana cultivation. However, during the propagation process, banana crops have presented limitations such as low bud stimulation, high phenolic oxidation rate. This research was carried out in the Tissue Culture Laboratory of the INIAP Tropical Pichilingue Experimental Station. It aimed to assess the effect of the size of explanation on the rate of in vitro multiplication of plants in two banana crops. The banana crops studied were Dominico Hartón (Musa AAB Simmonds) and Hartón (Musa AAB), with two sizes of explants (0.5-1.00 and 1.5-2.0) cm. The experimental DCA design was used with 4 repetitions plus two controls. The Tukey test was applied at a 95% probability. Murashige and Skoog culture medium was felt. The variables of percentage of contamination, days to rupture of apical dominance (rdp), number of explanations at rdp, number of explanations per replicate, number of explanations with lateral buds and propagation factor were evaluated. Once the results were obtained, the treatments studied in the establishment phase were not contaminated, the initial explanation size that presented the greatest number of days at rdp was 0.5-1.0 cm, with an average of 30 dds, and a general average number of explants was obtained at rdp 2 explants, for each initial explainer. The results indicate that the Hartón cultivar with the initial explant size 0.5-1.0 cm indicates the greatest number of shoots prior to each peal, with an average of 307 explants, with a propagation factor of 3.5 shoots for each explant. Keywords: In vitro, cultivars, explant, repique